التعليم والتربية في الفكر الفلسفي اليوناني (Comprehensive Journal of Science, 2026)
This study aims to analyze the philosophical foundations of education in ancient Greek thought by examining the educational conceptions of Socrates, Plato, and Aristotle and highlighting their contribution to the formation of educational theory. The study adopts a descriptive-analytical approach to explore the relationship between philosophy and education and to demonstrate how education evolved from a traditional social practice into a comprehensive philosophical project aimed at shaping the rational and virtuous human being. The findings reveal that Socrates established dialogue as a method for developing critical thinking, Plato designed a structured educational system linked to justice within the state, and Aristotle presented a realistic approach based on balance between moral and intellectual virtues. The study concludes that Greek educational thought constitutes a fundamental basis for understanding the development of modern educational theory and remains a valuable reference for rethinking contemporary educational goals.
Keywords: Greek philosophy, philosophy of education, Socrates, Plato, Aristotle, educational thought, justice, dialogue